Optimal time for COVID-19 vaccination in rituximab-treated dermatologic patients - Seree-aphinan, Chutima; Ratanapokasatit, Yanisa; Suchonwanit, Poonkiat; Rattanakaemakorn, Ploysyne; O-Charoen, Pichaya; Pisitkun, Prapaporn; Suangtamai, Thanitta; Setthaudom, Chavachol; Chirasuthat, Sonphet; Chanprapaph, Kumutnart (Frontiers in Immunology, 2023)
Background By depleting circulating B lymphocytes, rituximab time-dependently suppresses coronavirus disease 2019 (COVID-19) vaccines’ humoral immunogenicity for a prolonged period. The optimal time to vaccinate rituximab-exposed immune-mediated dermatologic disease (IMDD) patients is currently unclear. Objective To estimate the vaccination timeframe that equalized the occurrence of humoral immunogenicity outcomes between rituximab-exposed and rituximab-naïve IMDD patients. Methods This retrospective cohort study recruited rituximab-exposed and age-matched rituximab-naïve subjects tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific immunity post-vaccination. Baseline clinical and immunological data (i.e., immunoglobulin levels, lymphocyte immunophenotyping) and SARS-CoV-2-specific immunity levels were extracted. The outcomes compared were the percentages of subjects who produced neutralizing antibodies (seroconversion rates, SR) and SARS-CoV-2-specific IgG levels among seroconverters. The outcomes were first analyzed using multiple regressions adjusted for the effects of corticosteroid use, steroid-spearing agents, and pre-vaccination immunological status (i.e., IgM levels, the percentages of the total, naïve, and memory B lymphocytes) to identify rituximab-related immunogenicity outcomes. The rituximab-related outcome differences with a 95% confidence interval (CI) between groups were calculated, starting by including every subject and then narrowing down to those with longer rituximab-to-vaccination intervals (≥3, ≥6, ≥9, ≥12 months). The desirable cut-off performances were <25% outcome inferiority observed among rituximab-exposed subgroups compared to rituximab-naïve subjects, and the positive likelihood ratio (LR+) for the corresponding outcomes ≥2. Findings Forty-five rituximab-exposed and 90 rituximab-naive subjects were included. The regression analysis demonstrated a negative association between rituximab exposure status and SR but not with SARS-CoV-2-specific IgG levels. Nine-month rituximab-to-vaccination cut-off fulfilled our prespecified diagnostic performance (SR difference between rituximab-exposed and rituximab-naïve group [95%CI]: -2.6 [-23.3, 18.1], LR+: 2.6) and coincided with the repopulation of naïve B lymphocytes in these patients. Conclusions Nine months of rituximab-to-vaccination interval maximize the immunological benefits of COVID-19 vaccines while avoiding unnecessary delay in vaccination and rituximab treatment for IMDD patients.